(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article discusses the components of the educational environment in the development of the communicative culture of students, the pedagogical process in the educational environment, dialogic communication based on activities between educational subjects, public speaking, classroom teaching and extracurricular training, innovative teaching technologies developed on the basis of a psychodidactic approach, as well as theoretical and practical foundations of methods for combining didactic and psychological content based on the principle of generalization, developing innovative communication and its implementation.